Per un’estetica del turismo gastronomico: dall’autenticità dell’esperienza turistica alla qualità dell’esperienza estetica - Bertino, Pietro (Scenari, 2025)
This paper explores the phenomenon of mass tourism from an aestheticological standpoint, focusing specifically on gastronomic tourism as a case study. The goal is to demonstrate that the tourist experience is not merely about the diverse range of activities associated with tourism, but rather reflects a broader framework for understanding experience, deeply rooted in modern Western thought. The emergence of philosophical aesthetics shares with tourism not only a chronological overlap but also the modern drive to epistemologize reality. From the Grand Tour to its massified contemporary counterpart and the current trend of compulsive gastronomic consumption, the modern subject seeks to know—or recognize —the world, deriving social benefits from this knowledge. Thus, it can be argued that tourist experiences do not inherently possess aesthetic value; rather, their aesthetic potential is subordinated to a (re)cognitive imperative. In addition, we must question whether tourism is evolving into a perceptual habitus that shapes our overall mode of experience.